State of Transport Administrative Structure in Lagos, Ogun and Oyo States, Nigeria - Obafemi Salisu, Umar (Journal of Tourism, Sustainability and Well-being, 2019)
A well-organised transport administrative structure serves as a necessary tonic for transport system development of any society. This study identifies existing state of transport administration and major challenges facing transport administrative structure in Lagos, Oyo and Ogun States, Nigeria. It adopted cross-sectional research design and anchored on both primary and secondary sources of data. Transport administrative structure (consolidation and unbundling designs) were used to show state of transport administration operating in the selected States, while Analysis of Variance (ANOVA) was used to prove statistical variation among problems associated with transport administrative structure. Findings revealed that the transport administrative structure in the selected States is not uniform as Lagos State operates consolidation design; Ogun State follows unbundling design; while Oyo State operates on neither consolidation nor unbundling designs. Findings further revealed that fragmented administrative bodies with overlapping responsibilities; incomplete supervision mechanisms; corruption and mismanagement of funds are major challenges affecting existing transport administrative structure. ANOVA result shows significant variation among the observed problems. Thus, study recommends that Ministry and Agencies in charge of transport systems should run on consolidated structure that allows for easy day-to-day planning, monitoring and coordination of various transport modes under one administrative body.